A synthesis of the current knowledge on the Australian Orchesellidae (Collembola, Entomobryoidea) - Bellini, Bruno Cavalcante; Greenslade, Penelope; Baquero, Enrique; Jordana, Rafael; de Souza, Paolla Gabryelle Cavalcante (Zootaxa, 2022)
The Australian Orchesellidae includes only 11 nominal species in four genera: Australotomurus Stach, 1947, Alloscopus Börner, 1906, Heteromurus Wankel, 1860, and Falcomurus Mandal, 2018. Here we describe Dicranocentrus dolosus sp. nov. from Cocos and Keeling Islands, the first species of the genus to be recorded from Australia. The new species is similar to D. inermodentes (Uchida, 1944) and D. indicus Bonet, 1930, but differs from both by the combination of the ventral head, mesothoracic and dental chaetotaxy. We also revisit Australotomurus based on previous studies to better interpret the dorsal macrochaetotaxy of the genus, and provide a synthetic map of chaetae to guide future studies on scaleless Orchesellidae. Finally, we present updated diagnoses to all genera and species of Australian Orchesellidae, as well as an identification key to all species.